2023
DOI: 10.1021/acsanm.3c00067
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Serum Albumin-Coated Ceria Nanoparticles Activate the TGF-β Signaling Pathway for Periodontal Bone Regeneration

Abstract: Heterogeneous human periodontal ligament cells (hPDLCs) are the key seed cells to address the regeneration of periodontal bone defects, and nanomaterials b ring strategies for periodontal bone regeneration. Herein, we synthesized cerium-based nanoparticles by a convenient, green, and efficient bovine serum albumin (BSA) culture strategy. The results of in vitro experiments showed that CeO2@BSA had a significant ability to promote osteogenesis in hPDLCs at lower concentrations, which was mediated through TGF-β … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…The nanocomposite system exhibited efficient osteogenic differentiation to repair and regenerate defective periodontal bone tissue. They have reported that cerium oxide-based nanocomposite systems would be excellent materials for bone tissue engineering …”
Section: Applications Of Protein In Bone Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanocomposite system exhibited efficient osteogenic differentiation to repair and regenerate defective periodontal bone tissue. They have reported that cerium oxide-based nanocomposite systems would be excellent materials for bone tissue engineering …”
Section: Applications Of Protein In Bone Tissue Engineeringmentioning
confidence: 99%
“…(D) The proposed nanocomposite system via TGF-β signaling pathway and autophagy activation for periodontal bone repair and regeneration. (Reproduced with permission from ref , Copyright 2023, American Chemical Society. )…”
Section: Applications Of Protein In Bone Tissue Engineeringmentioning
confidence: 99%
“…Both the excellent targeting properties and superior biosafety of appropriately modified nanoparticles are advantageous for regulating autophagy. , Nucleic acid inducers (NucA, AS1411) are small oligonucleotide fragments that are the first anticancer aptamers to be tested in clinical trials (phase I and II clinical trials). , NucA has been widely employed as a tumor-targeting agent that can be conjugated into a wide variety of molecules and nanomaterials. NucA normally interacts with nucleolar proteins in the nucleus, but nucleolar proteins are also expressed on the surface of cancer cells . Therefore, NucA could be used as a new avenue to develop a targeted nanotherapeutic platform for ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%